THE EFFECT OF SLEEPING IN THE DARK ON SLEEP QUALITY IN FACULTY OF MEDICINE UNIVERSITAS ISLAM BANDUNG INDONESIA STUDENTS - Rahmawaty Alie, Ike; Widayanti; Islami, Umar; Ghin Anugrah, Ghin; Nurlita, Talia (Fakultas Kedokteran Gigi Unjani, 2025)
Sleep is a state where the body experiences active unconsciousness, at this time the brain is in a relative rest phase but will remain reactive to internal stimuli. Sleeping in the dark can increase melatonin which affects sleep quality and results in fitness later. This study aims to see the effect of sleeping in the dark on sleep quality and fitness in 4th year medical students Bandung Islamic University. This study is experimental by comparing sleep quality and fitness when sleeping in light and dark conditions. The study was conducted on 42 students of Faculty of Medicine, Unisba. The students previously slept in light conditions and their sleep quality and fitness were measured after being asked to sleep in the dark with a special eye mask for 2 weeks. Sleep quality was assessed using the PSQI questionnaire that were translated in Indonesian language. The results of the study found that there was a significant difference in sleep quality (p<0.01). Sleeping in the dark can lead to good sleep quality might be because melatonin production is optimized, helping us fall asleep faster and stay asleep longer. DOI : 10.54052/jhds.v4n3.p239-246